Algorithm design for the fleet sizing problem in grocery retail distribution - Tiago Miguel Ladeiras Beleza de Vasconcelos (2019)
From the classical Vehicle Routing Problem (VRP) and other extensions as well, our research will focus on constraints within grocery retail distribution. Usually they are tackled in the literature as VRP with multiple compartments and multiple trip VRP. Furthermore, we will cope with time windows and other extensions. In addition, our problem will be stated and a solution proposal will be sketched, both considering heuristic and exact approaches.